A corporate social responsibility (CSR) model – a QFD-based approach. (2nd January 2020) - Zaitsev, Natalia; Dror, Shuki
Abstract : Corporate social responsibility (CSR) strategies encourage the company to make a positive impact on the environment and stakeholders, which include consumers, employees, investors, communities and others. To enrich the practice of CSR initiatives, we developed an approach for examining the relationship between various CSR indicators (CSRIs) and outcomes for a specific enterprise, based on the quality function deployment (QFD) method. For a specific business case (data were collected from a manufacturing plant in the chemical engineering and energy industry), an adapted House of Quality (HOQ) matrix was created using a combined input from various senior and line managers. This matrix summarises the desired improvements in the CSR results and connects them to the relevant reportable CSRIs. Based on the HOQ matrix, indicators and outcomes that maximise the desired results of the CSR policy were chosen using the mean square error criterion. We found that when utilising the QFD-based approach, the business could quantify strategic priorities regarding CSR initiatives. The applied approach offers a scientific/engineering method for identifying a subset of vital CSRIs necessary to achieve the best CSR outcomes for all types of businesses at all stages of their development.